2021
DOI: 10.3390/jcm10194439
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain in Hand Osteoarthritis: A Cross-Sectional Study

Abstract: Symptomatic hand osteoarthritis (OA) is a severely debilitating condition. Neuropathic pain (NP) has been shown to be a factor affecting pain severity, hand function, psychological wellbeing, body schema, and the number of pain medications in people with OA of other joints. The aim of this study was to assess the prevalence of NP in symptomatic hand OA and assess its association with pain, hand function, measures of psychological wellbeing, sleep, body schema disturbances, and number of pain medications. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…We also used two other questionnaires: DN4 and PainDETECT, as well as NPSI, which was specifically designed to evaluate NP. A previous study used the DN4 questionnaire and found that 42% of patients with hand OA experienced NP [9], in line with our own findings using the same questionnaire. Another study previously used the PainDETECT questionnaire and reported an NP frequency of 19% in patients with hand OA [10], which is lower than that observed in our study (32.4%) using this questionnaire.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also used two other questionnaires: DN4 and PainDETECT, as well as NPSI, which was specifically designed to evaluate NP. A previous study used the DN4 questionnaire and found that 42% of patients with hand OA experienced NP [9], in line with our own findings using the same questionnaire. Another study previously used the PainDETECT questionnaire and reported an NP frequency of 19% in patients with hand OA [10], which is lower than that observed in our study (32.4%) using this questionnaire.…”
Section: Discussionsupporting
confidence: 91%
“…In subjects affected by knee OA, NP correlates with the severity of symptoms, joint function, psychological well-being, and the intake of painkillers [ 7 , 8 ]. Although understudied, it has been reported that NP may occur in 16–42% of patients with hand OA using different assessment questionnaires [ 9 , 10 ]. In the Magni N et al cohort of 121 patients with symptomatic hand OA, the prevalence of NP was estimated at 42% using the Douleur Neuropathique en 4 Questions (DN4) questionnaire [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nervous system serves as the primary system for sensing and transmitting pain signals throughout the body. Recent research has indicated a higher prevalence of neuropathic pain (NP) in individuals with OA ( 124 , 125 ), where OA may lead to stimulation or damage of nerve endings located within or surrounding the joints, resulting in persistent or intermittent pain ( 126 ). These pain-related manifestations could potentially prompt changes in neural excitability, alterations in neurotransmitter release, and reduced neural plasticity ( 127 ).…”
Section: Oa and Nervous System Diseasementioning
confidence: 99%
“…Hand osteoarthritis (OA) is a debilitating joint disease. 1,2 It is the second most prevalent form of OA, with only knee OA being more prevalent. 3 By the time they reach 85 years of age, 40% of adults are estimated to be affected by hand OA.…”
Section: Introductionmentioning
confidence: 99%
“…Hand osteoarthritis (OA) is a debilitating joint disease 1,2 . It is the second most prevalent form of OA, with only knee OA being more prevalent 3 .…”
Section: Introductionmentioning
confidence: 99%